Perspectives on the infringement of criminal laws by adolescents following the use of drugs or hallucinogenic substances in Puerto Maldonado, Peru - Huamán, Luz Marina Almanza; Roque, Diana Milagros Duenas (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the research is to determine and describe the influence of drug use in adolescents to infringe and commit criminal offenses in the province of Tambopata. The design used in this research is quantitative, descriptive and analytical to perform a critical analysis and a non-experimental design was used. The methodology used are direct interviews with the officials who handle these cases of infractions such a judges and lawyers, a multiple choice survey interview was used for the dimension of drug use and a dichotomous option survey was used for the dimension of criminal infractions. The surveys were conducted directly with an interview in which the answers on drug use and criminal offenses were filled in. As main result it was found that there are significant effects before and after drug use in adolescents, and as preferred places for consumption are squares or parks, and the main instigators are friends or classmates, family abandonment and others who promote drug use. It was concluded that there should be more control in educational institutions as student tutoring centers. One of the limitations was not having direct access to interviews with those involved.